The Influence of Internal Controls on Management Models in Increasing the Efficiency of Public Water Supply - Kobešćak, Zoran (Digital Repository of Theses, 2025)
Public water supply in modern times, meaning words, has existed since 1544, when the English parliament brought an insurance law to clear water for citizens in London. In the middle of the 19th century, under the influence of the Industrial Revolution, cities were rapidly developed, and the number of inhabitants and economic activities grew due to the need for water. With accelerated growth in population, urbanization, polluted environment, and already those present effects of climatic change, it is getting harder to ensure and keep enough drinks water. Water supply companies face a challenge to establish a balance between efficient distribution water supply mesh and efficiency in using natural, human, financial and other resources, a responsible are for realization goals sustainable and effective of business. The problem of efficiency and sustainability of public water supply is a global problem, and water loss is generally considered an important question. Losses of water present in all water supply systems are caused by a series of operational and procedural reasons, especially the fact that in most water supply organizations losses, water with time growing or others in words efficiency quiet organization decreases. Water supply systems have become more prominent, and everything is older. Because of that, they are, consequently, all more complex for monitoring, management, and maintenance. Repercussions like that state are continuous growth negative indicators of the business. In their efforts to improve your business, water supply companies use different approaches that mostly bring down rehabilitation breakdowns in the fight against water losses. Loss management will be water successful only if introduced as part of the whole sustainable package measure defined long-term strategy. At the same time, when the working group strives to find solutions to increase the efficiency of public water supply, two new ones appeared in the global economic field, each with an independent concept, which entries significant improvements in business economic subjects. Concepts of Lean and Green Management and Industries 4.0 are becoming imperative success businesses and are not deviously part of the production environment but are leading production strategies worldwide. By applying principles of Lean and green management and digitization business based on new ICT technologies, they improved existing methods for efficient water supply management. By occasionally recognizing potential risks and introducing new processes, you reduce the same to an acceptable level, and we influence the efficient water supply system management.